2017
DOI: 10.5606/archrheumatol.2017.5919
|View full text |Cite
|
Sign up to set email alerts
|

Which Predicts Quadriceps Muscle Strength in Knee Osteoarthritis: Biological Markers or Clinical Variables?

Abstract: Objectives: This study aims to evaluate the relationship between biological markers and quadriceps muscle strength, the correlation of clinical variables with quadriceps muscle strength, and the results according to the radiological severity in patients with knee osteoarthritis. Patients and methods: A total of 152 patients (22 males, 130 females; mean age 57.3±7.5 years; range 40 to 70 years) with primary knee osteoarthritis were included in the study. We evaluated biological markers of C-telopeptide of type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…We also found significant negative correlation between VAS values and isokinetic measurements (peak torque, average power of patients' knee extensors and flexors and total work of knee extensors). Gokcen et al [29] studied the correlation of peak torque of knee extensor and flexor muscles and VAS in 152 OA patients. They found that the VAS of pain was weakly to moderately correlated with the parameters of isokinetic test (r-values ranging from -0.22 to -0.33).…”
Section: Discussionmentioning
confidence: 99%
“…We also found significant negative correlation between VAS values and isokinetic measurements (peak torque, average power of patients' knee extensors and flexors and total work of knee extensors). Gokcen et al [29] studied the correlation of peak torque of knee extensor and flexor muscles and VAS in 152 OA patients. They found that the VAS of pain was weakly to moderately correlated with the parameters of isokinetic test (r-values ranging from -0.22 to -0.33).…”
Section: Discussionmentioning
confidence: 99%